FAKTOR YANG MEMPENGARUHI AUDIT JUDGMENT DENGAN OBEDIENCE PRESSURE SEBAGAI PEMODERASI - Prihatiningtias, Yeney Widya; Putri, Aliyah Alamanda (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2025)
This research aims to determine the effect of ego depletion, moral reasoning, and goal orientation on audit judgement with obedience pressure as a moderating variable and self-efficacy as a mediating variable. The research data are collected through census utilizing questionnaires, and the samples include 116 auditors of East Java Provincial Representative BPKP. The data obtained are analysed by testing descriptive statistical and inferential analysis utilizing the PLS-based SEM approach processed by SmartPLS. The results of the research exhibit that ego depletion, performance approach goal orientation, and performance avoidance goal orientation have a negative and significant effect; self-efficacy has a positive and significant effect; and learning goal orientation and moral reasoning have no effect on audit judgement. Self-efficacy mediates the effect of goal orientation on audit judgement; and obedience pressure moderates the effect of self-efficacy, but does not moderate the effect of ego depletion and moral reasoning on audit judgement.